Objective ofWorld Class Manufacturing (WCM) - Zero Breakdown, Accident, Defect (BAD) is Myth or Real - Nachiappan, RM.; Muthukumar, N. (Gyan Management Journal, 2016)
In the era of globalization with major players from all over the world, the term world class is appropriate. World Class Manufacturing (WCM} is a term widely recognized in manufacturing, e11compassing a wide range of activities. Among the identified 50 continuous improvement (CI) tools, by adopting the best maintenance proctice CI tool Total Productive Maintenance {TPM) in aneffective and systematic manner will have an impact over the WCM objective. The general methodology of achieving the WCM objective of zero break down; Zero accident; Zero defect (BAD) has been illustrated in stages and also to make it in to regular practice curriculum for industries, ''Attitude, Behavior and Culture (ABC)" new innovative approach has been enumerated practically.
Keywords: Continuous improvement; Total Productive Maintenance; Culture; Innovative approach; Jishuhozen